HUBUNGAN ASUPAN MAKAN, DURASI TIDUR DAN AKTIVITAS FISIK DENGAN STATUS GIZI KARYAWAN TOKO RITEL KOTA BATAM TAHUN 2023 - Liya Anjelina; Gunawan, Dahlan; Luckie Loveanis (Universitas Batam, 2024)
Background: Nutritional status remains a global issue, including in Indonesia. Nutritional status is influenced by several factors, namely food intake, sleep duration, and unbalanced physical activity, which can lead to either excessive or insufficient nutritional status. This study aims to investigate the relationship between dietary intake, sleep duration, and physical activity with the nutritional status of retail store employees in Batam City in 2023. Methods: This research is a cross-sectional analytical study with accidental sampling technique involving 60 samples. Food intake is measured using a semi-qualitative Food Frequency Questionnaire (FFQ), sleep duration is measured using a questionnaire on average weekly sleep duration, physical activity is measured using the Global Physical Activity Questionnaire (GPAQ), and nutritional status is measured using the Body Mass Index (BMI) by measuring weight and height. Data analysis using correlation gamma test. Results: The correlation gamma test results indicate a significant relationship between food intake and nutritional status with a p-value of 0.000 (p ≤ 0.05)(r=0,919). However, the relationship between sleep duration and nutritional status resulted in a p-value of 0.137 (p > 0.05)(r = -0,284), and the relationship between physical activity and nutritional status resulted in a p-value of 0.758 (p>0.05)(r = -0,067). Conclusion: There is a significant relationship between food intake and the nutritional status of retail store employees in Batam City in 2023. However, there is no significant relationship between sleep duration, physical activity, and the nutritional status of retail store employees in Batam City in 2023. Keywords: Nutritional Status, Food Intake, Sleep Duration, Physical Activity